Reliable extraction of a deepwater trace metal isotope signal from Fe-Mn oxyhydroxide coatings of marine sediments - Gutjahr, M; Frank, M; Stirling, C; Klemm, V; van de Flierdt, T; Halliday, A (2007)
The extraction of a deepwater radiogenic isotope signal from marine sediments is a powerful, though under-exploited, tool for the characterisation of past climates and modes of ocean circulation. The radiogenic and radioactive isotope compositions (Nd, Pb, Th) of ambient deepwater are stored in authigenic Fe-Mn oxyhydroxide coatings in marine sediments, but the unambiguous separation of the isotopic signal in this phase from other sedimentary components is difficult and measures are needed to ensure its seawater origin. Here the extracted Fe-Mn oxyhydroxide phase is investigated geochemically and isotopically in order to constrain the potential and the limitations of the reconstruction of deepwater radiogenic isotope compositions from marine sediments. Our results show that the isotope compositions of elements such as Sr and Os obtained from the Fe-Mn oxyhydroxide fraction are easily disturbed by detrital contributions originating from the extraction process, whereas the seawater isotope compositions of Nd, Pb and Th can be reliably extracted from marine sediments in the North Atlantic. The main reason is that the Nd, Pb and Th concentrations in the detrital phase of pelagic sediments are much lower than in the Fe-Mn oxyhydroxide fractions. This is reflected in Al/Nd, Al/Pb and Al/Th ratios of the Fe-Mn oxyhydroxide fractions, which are as low as or even lower than those of hydrogenetic ferromanganese crusts. Mass balance calculations illustrate that the use of the 87Sr/86Sr isotope composition to confirm the seawater origin of the extracted Nd, Pb and Th isotope signals is misleading. Even though the 87Sr/86Sr in the Fe-Mn oxyhydroxide fractions is often higher than the seawater Sr isotope composition, the corresponding detrital contribution does not translate into altered seawater Nd, Pb and Th isotope compositions due to mass balance constraints. Overall the rare earth element patterns, elemental ratios, as well as the mass balance calculations presented here highlight the potential of using authigenic Fe-Mn oxyhydroxide coatings as paleoceanographic archives for the analysis of past seawater Nd, Pb and Th isotope compositions. © 2007 Elsevier B.V. All rights reserved.